Nosí orel děti?: příspěvek k porozumění mezopotámskému Mýtu o Etanovi = Does the eagle bring children? : a contribution to understanding the Mesopotamian Myth of Etana - Koubková, Evelyne (Religio, 2015)
This paper deals with the ancient Mesopotamian Myth of Etana. The main problem of interpretation lies in linking the different parts of the myth together. Therefore, my aim is to investigate the possibilities of understanding the myth as a whole, in which every part of the story is essential. By viewing it structurally, I present its motives as being interconnected, at the same time taking into account the development of the narrative. In my view, Etana becomes king throughout the whole myth, not just once at its beginning. Since kingship is a mediatory role, Etana has to relate himself to the godly as well as to the natural spheres. His healing of an eagle represents a new, healthy relationship with nature. I argue that the eagle is symbolically attached to the begetting of children, on the basis of wordplay in Akkadian which reminds us of the so called aetites, eagle stones. The eagle, a symbol of pregnancy, becomes domesticated and helps Etana acquire offspring. Their ensuing flight to heaven represents Etana's acquisition of royal insignia and at the same time of godly blessing in general. His becoming king and begetting offspring appear, in fact, to be the same turning points within the story, viewed from different perspectives. On another level, the myth can be seen as aetiological. Since the scene of Etana's healing of the eagle is loaded with birth symbolism, the eagle can become the one who helps others beget and give birth to children.